Anti-angiogenic and toxicity effects of Derris trifoliata extract in zebrafish embryo - Wan Sulaiman, Wan Mohd. Azizi; Unal, Kevser (2018)
Introduction: Derris trifoliata has been traditionally used as folk for the treatment of , rheumatic joints, diarrhoea, and dysmenorrhea, and rotenoids isolated from the plant have shown to exhibit anti-cancer properties. This study aimed to assess the toxicity effects and antiangiogenic activity of extract of Derris trifoliata on zebrafish embryo model. Materials and Methods: Zebrafihs embryos were treated with aqueous extract of Derris Trifoliata to evaluate its effects on angiogenesis and zebrafish-toxicity. Angiogenic response was analyzed using whole-mount alkaline phosphatase (AP) vessel staining on 72 hours post fertilization (hpf) zebrafish embryos. Results: 1.0 mg/ml concentration was toxic to zebrafish embryos and embryos exposed to concentrations at 0.5 mg/ml and below showed some malformations. Derris trifoliata aqueous extract also showed some anti-angiogenic activity in vivo in the zebrafish embryo model wereby at high concentration inhibited vessel formation in zebrafish embryo.